2022
DOI: 10.1038/s41531-022-00328-5
|View full text |Cite
|
Sign up to set email alerts
|

Short chain fatty acids-producing and mucin-degrading intestinal bacteria predict the progression of early Parkinson’s disease

Abstract: To elucidate the relevance of gut dysbiosis in Parkinson’s disease (PD) in disease progression, we made random forest models to predict the progression of PD in two years by gut microbiota in 165 PD patients. The area under the receiver operating characteristic curves (AUROCs) of gut microbiota-based models for Hoehn & Yahr (HY) stages 1 and 2 were 0.799 and 0.705, respectively. Similarly, gut microbiota predicted the progression of Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 74 publications
3
45
0
Order By: Relevance
“…There are more than 20 studies on gut microbiota in patients with PD and iRBD reported by us 19 22 and others 23 40 , but gut microbiota in DLB has not been reported to the best of our knowledge. We previously showed by meta-analysis of gut microbiota in different countries that mucin-degrading genus Akkermansia was increased in PD and iRBD, while short chain fatty acids (SCFA)-producing genera Faecalibacterium and Roseburia were decreased in PD but not in iRBD 20 , 21 .…”
Section: Introductionmentioning
confidence: 88%
“…There are more than 20 studies on gut microbiota in patients with PD and iRBD reported by us 19 22 and others 23 40 , but gut microbiota in DLB has not been reported to the best of our knowledge. We previously showed by meta-analysis of gut microbiota in different countries that mucin-degrading genus Akkermansia was increased in PD and iRBD, while short chain fatty acids (SCFA)-producing genera Faecalibacterium and Roseburia were decreased in PD but not in iRBD 20 , 21 .…”
Section: Introductionmentioning
confidence: 88%
“…In a recently published study, Nishiwaki and colleagues investigated the manner in which short-chain fatty acid-producing and mucin-degrading intestinal bacteria predict the progression of early PD [ 32 ]. They report that decreases in short-chain fatty acid-producing genera, Fusicatenibacter, Faecalibacterium and Blautia, as well as an increase of the mucin-degrading genus Akkermansia, predicted accelerated disease progression.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…1XD42-69, Eubacterium sp. 14 − 2, and Lachnospiraceae bacterium A4 (Morrison and Preston, 2016;Tamanai-Shacoori et al, 2017;Nishiwaki et al, 2020Nishiwaki et al, , 2022. On the other hand, Alistipes sp.…”
Section: Discussionmentioning
confidence: 99%